About a discussion ââDevelopment a new mutation operator to solve the Traveling Salesman Problem by aid of genetic algorithmsââ, by Murat Albayrak and Novruz Allahverdi, (2011). Expert System with Applications (38) (pp. 1313â1320) - Allahverdi, Novruz (International Journal of Intelligent Systems and Applications in Engineering, 2015)
In the Short Communication published in âExpert Systems with Applicationâ in volume 41 2014, (Comments on "Albayrak, M., & Allahverdi N. (2011). Development a new mutation operator to solve the Traveling Salesman Problem by aid of Genetic Algorithms. Expert Systems with Applications, 38(3), 1313-1320": A Proposal of Good Practice; E. Osaba, E. Onieva, F. Diaz, R. Carballedo, Volume: 41, Issue: 4, Pages: 1530-1531, Part: 1, MARCH 2014) the Osoba E. et al have discussed our method to solve the Traveling Salesman Problem pointing that we use our developed new algorithm to compare different versions of a classical genetic algorithm, each of one with a different mutation operator and they write that this can generate some controversy. Here we shortly analyze the comment of Osaba E. et al to show that our comparing method has a chance of existence.